THE DETERMINATION OF SOURCE MECHANISMS OF SMALL EARTHQUAKES BY MOMENT TENSOR INVERSION - Malytskyy, D.; Mikesell, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A method is presented for moment tensor inversion of only direct P-waveforms registered at only one station and a limited number of stations. The method is based on an inversion approach described in where a version of the matrix method has been developed for calculation of direct P-waves in horizontally layered half-space from a point source represented by its moment tensor. We describe a procedure for retrieving the source mechanism of small earthquakes based on interactive inversion of seismograms and demonstrate its application to two local earthquakes in the Boise region. The moment tensor inversion of seismogram data in this study is based on a point source model. The process includes generation of synthetic seismograms using the matrix method for an elastic, horizontallylayered, medium. In the paper, a method is presented for moment tensor inversion of only direct P- waves, which are less sensitive to path effects than reflected and converted waves. This approach significantly improves the inversion method accuracy and reliability. A pointsource approximation is considered, with known location and origin time. Based on forward modeling, a numerical technique is developed for the inversion of observed waveforms for time history of the components of moment tensor M(t), obtained by generalized inversion.
Keywords: seismic moment tensor; source mechanism; small earthquakes; matrix method